Regulatory network of ammonium and nitrate uptake and utilization in rice - Guo, Xiaoli; Zhang, Ju; Ma, Feilong; Li, Pengxiang; Ma, Yunlong; Xu, Kedong; Liu, Ti (Frontiers in Plant Science, 2025)
Nitrogen (N) plays a crucial role in various aspects of crop growth, development, yield, and quality. It is essential for processes ranging from protein synthesis and photosynthesis to crop adaptation and stress tolerance, thereby having a profound impact on crop production. Crops primarily absorb N in the forms of ammonium (NH4+) and nitrate (NO3-), with NH4+ being the predominant form absorbed by flooded crops such as rice. This review focuses on rice and highlights recent significant advances in the mechanisms of N uptake and utilization, including the roles of NO3- and NH4+ transporters. Key transporters such as OsAMT1.1 and OsNRT1.1B play central roles in enhancing N uptake and improving N use efficiency (NUE). Furthermore, natural allelic variations in genes such as DNR1 and OsWRKY23 underlie the differences in NUE between indica and japonica subspecies. We also discuss the potential of multi-gene pyramiding strategies, such as OsAMT1.2×OsGS1.2×OsAS1, to synergistically improve NUE through coordinated regulation of N uptake, assimilation, and remobilization. Collectively, this review systematically summarizes the functions and regulatory mechanisms of key NUE-related genes in rice, providing valuable gene resources and a theoretical foundation for the molecular breeding of N-efficient rice varieties.